An Unusual Presentation of Lupus in a Pediatric Patient - Vimal Master Sankar Raj (Hindawi Limited, 2013)
Systemic lupus erythematosus (SLE) is an autoimmune disease causing inflammatory tissue damage. Multiple organ damage can ensue with renal and neurological involvement carrying the worse prognosis. In this case report we present a 10-year-old African American girl who presented with abnormal choreiform movements, headache, weight loss, and fatigue. Detailed clinical examination with laboratory and imaging studies clinched the diagnosis of SLE. Echocardiogram revealed the presence of Libman-sacks endocarditis. Patient showed rapid resolution of symptoms with steroid therapy. A brief discussion on childhood onset lupus along with the varied clinical presentation is discussed.